(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the language aesthetic symbols Skovoroda, Franko, Shevchenko, Taras, Kobzar, Kyiv, Dnipro, Babyn Yar, and pussy-willow used in the poetic works of D. Pavlychko. They are used as national-precedent phenomena that are characteristic constituent of the lexical system of the author’s poetic speech.